Salidroside Ameliorates Alzheimer's Disease by Targeting NLRP3 Inflammasome-Mediated Pyroptosis - Cai, Yawen; Chai, Yuhui; Fu, Yu; Wang, Yingdi; Zhang, Yiming; Zhang, Xue; Zhu, Lingpeng; Miao, Mingxing; Yan, Tianhua (Frontiers in Aging Neuroscience, 2022)
Amyloid β-protein (Aβ) is reported to activate NLRP3 inflammasomes drive to pyroptosis, which is subsequently involved in the pathogenesis of neurodegenerative diseases, such as Alzheimer's disease (AD). Nevertheless, sadly, the pathogenesis of AD has been relatively insufficiently elucidated. Therefore, this study was conducted to explore whether Salidroside (Sal) treatment could benefit AD by improving pyroptosis. Firstly, two animal models of AD, induced respectively by Aβ1-42 and D-galactose (D-gal)/AlCl3, have been created to assist our appreciation of AD pathophysiology. Then we confirmed the pyroptosis is related to the pathogenesis of AD, and Sal can slow the progression of AD by inhibiting pyroptosis. Subsequently, we established the D-gal and Nigericin-induced PC12 cells injury model in vitro to verify that Sal blocks pyroptosis mainly by targeting the NLRP3 inflammasome. For the in vivo studies, we observed that Aβ accumulation, Tau hyperphosphorylation, neurons of hippocampal damage, and cognitive dysfunction in AD mice, caused by bilateral injection of Aβ1-42 into the hippocampus and treatments with D-gal combine AlCl3. Besides, accumulated Aβ promotes NLRP3 inflammasome activation, which leads to the activation and release of a pro-inflammatory cytokine, interleukin-1 beta (IL-1β). Notably, decreased both Aβ accumulation and hyperphosphorylation of Tau and inhibited pyroptosis by downgrading the expression of IL-1β and IL-18 can be attributed to the treatment of Sal. We further found that Sal can reverse the increased protein expression of TLR4, MyD88, NF-κB, P-NF-κB, NLRP3, ASC, cleaved Caspase-1, cleaved GSDMD, IL-1β, and IL-18 in vitro. The underlying mechanism may be through inhibiting TLR4/NF-κB/NLRP3/Caspase-1 signaling pathway. Our study highlights the importance of NLRP3 inflammasome-mediated pyroptosis in AD, and how the administration of pharmacological doses of Sal can inhibit NLRP3 inflammasome-mediated pyroptosis and ameliorates AD. Thus, we conclude that NLRP3 inflammasome-mediated pyroptosis plays a significant role in AD and Sal could be a therapeutic drug for AD.